Costa Rica's practice in its treaties to avoid double taxation - Pacheco Castro, Johnny (2025)
This article deals with the practice that Costa Rica has had in its negotiation and signing of treaties to avoid double taxation. Additionally, it analyzes the existing differences in the different treaties to avoid double taxation signed by Costa Rica and the application that has been given in the country of such treaties by the judicial and administrative bodies.